Stevens-Johnson syndrome and toxic epidermal necrolysis in pregnant patients: A systematic review - Ajay N. Sharma, BS; Bobak Hedayati, BS; Natasha A. Mesinkovska, MD, PhD; Scott Worswick, MD (Wolters Kluwer, 2020)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are two of the most severe dermatologic emergencies. Although pregnant women comprise a subset of individuals at risk for SJS and TEN development, little is known with regard to outcomes and treatment. Objective: This study aimed to conduct a systematic review to characterize the risk factors, outcomes, and treatment of SJS and TEN in pregnant patients and newborns. Methods: A primary literature search was conducted using PubMed in September 2019, using the following search terms entered in separate pairs: pregnant or pregnancy and stevens-johnson or SJS or toxic epidermal necrolysis. Reviews, studies in a language other than English, and articles not including pregnant patients were excluded. Results: Twenty-six articles were included for review, including a total of 177 patients. The average maternal age for a reaction was 29.9 years, gestational age was 24.9 weeks, and time to reaction after drug initiation was 27.5 days. Approximately 85% of pregnant women in this review were infected with HIV. The most common causative medications were antiretroviral therapy (90% of all cases), antibiotics (3%), and gestational drugs (2%). Of the 94 cases in which outcome data were available, the survival rates of pregnant women and newborns after delivery were 98% and 96%, respectively. Withdrawal of the offending agent and supportive care was often sufficient for treatment, but antibiotics, steroids, and intravenous immunoglobulin were implemented in some cases. Complications included preterm labor, vaginal stenosis, and vaginal adhesions. Conclusion: Given the predominance of studies focusing on the subset of pregnant patients who are infected with HIV, SJS and TEN is most commonly reported in young patients after antiretroviral therapy, primarily nevirapine. Overall mortality is lower than that of the general population, but similar to the expected mortality rates of younger adults. Early recognition and withdrawal of the offending agent is essential to mitigate the distinct consequences of these conditions in the pregnant population.